Method for testing corrosion performance of SiC fiber reinforced titanium-based composite material in marine environment

Through a variety of testing methods, including immersion experiments, electrochemical testing and microstructure analysis, the corrosion performance of SiC fiber-reinforced titanium-based composite materials in the marine environment was comprehensively evaluated, and the problems of long test cycles and incomplete evaluation in the existing technology were solved, and a comprehensive and accurate evaluation of corrosion performance and mechanism was achieved, providing reliable data support for the application of materials in the field of marine engineering.

CN119779959APending Publication Date: 2025-04-08LIAONING INST OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510044155.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When evaluating the corrosion performance of SiC fiber-reinforced titanium-based composites in marine environments, the test cycle is too long and it is difficult to meet the urgent needs of research and production, and traditional methods cannot comprehensively evaluate the corrosion performance and mechanism.

Method used

A variety of testing methods, including immersion experiments, electrochemical testing and microstructure analysis, were used to comprehensively evaluate the corrosion performance of SiC fiber-reinforced titanium-based composites in different marine environments. Parameters such as corrosion rate, electrochemical impedance and anode polarization curve were obtained through immersion experiments and electrochemical tests, and the corrosion mechanism was studied in combination with microscopic analysis methods.

Benefits of technology

It has achieved a comprehensive and accurate assessment of the corrosion performance of SiC fiber-reinforced titanium-based composite materials in the marine environment, provided more scientific data support, and provided more reliable data support for the application of materials in the field of marine engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119779959A_ABST
    Figure CN119779959A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material testing, and particularly discloses a method for testing the corrosion performance of a SiC fiber reinforced titanium-based composite material in a marine environment, and the method comprises the following steps: preparation of a SiC fiber reinforced titanium-based composite material sample, soaking experiment, electrochemical test and microstructure analysis. The corrosion performance of the SiC fiber reinforced titanium-based composite material in different marine environments can be comprehensively and accurately evaluated. Through soaking experiments and electrochemical tests, the corrosion rate, electrochemical impedance, anodic polarization curve and other parameters of the SiC fiber reinforced titanium-based composite material can be obtained, and more scientific data support is provided for related research. Meanwhile, by adopting different microanalysis methods, corrosion mechanisms in different marine environments can be further researched, and more reliable data support is provided for application of the SiC fiber reinforced titanium-based composite material in the field of marine engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material testing, and in particular relates to a method for testing the corrosion performance of a SiC fiber reinforced titanium-based composite material in a marine environment. Background Art

[0002] Continuous monofilament SiC fiber reinforced titanium-based composite materials have the advantages of high specific strength, high specific modulus, and high fatigue life, and have broad application prospects in the fields of aviation and deep sea. In recent years, the corrosion problem of materials used in the preparation of military aircraft and ships has become increasingly prominent.

[0003] For the study of marine atmospheric corrosion, it is currently common to establish a corrosion test station in a typical marine atmospheric environment for exposure testing. Exposure testing in a natural environment is the most effective experimental method for studying marine atmospheric corrosion. Through marine atmospheric exposure testing, the corrosion resistance and corrosion mechanism of different materials in different marine atmospheric environments can be understood, providing a reasonable and reliable design basis for material application. However, material corrosion damage in a natural environment is a long-term and continuous process, so the test cycle is long. For corrosion-resistant materials or protective layers, it often takes several years or even longer to obtain more reliable test data, which is difficult to meet the urgent needs of research and production, and is not conducive to the application of new materials.

[0004] In summary, the adaptability of the materials used to prepare military aircraft and ships to the harsh marine service environment will directly affect their service performance and service life. The marine adaptability of military aircraft and ships has become an important factor that cannot be ignored during design, development and final service. Only by fully understanding the corrosion behavior and mechanism of SiC fiber reinforced titanium-based composites in the marine environment can we optimize the manufacturing and protection process of SiC fiber reinforced titanium-based composites in my country in a targeted manner and improve the marine environment adaptability of military aircraft and ships.

[0005] At present, the test of SiC fiber reinforced titanium matrix composite materials includes exposure test in natural environment. By placing the materials in a corrosion test station in a typical marine atmosphere for long-term exposure, the corrosion of the materials in the actual marine environment can be truly reflected, providing a reliable design basis for material application. However, its biggest disadvantage is that the test cycle is too long. For corrosion-resistant materials or materials with protective layers, it often takes several years or even longer to obtain more accurate and reliable test data. Although the traditional immersion test can observe the corrosion degree and morphological changes of the materials in the marine simulated solution, there are certain limitations in relying on a single immersion test. On the one hand, its evaluation of the corrosion degree is not comprehensive enough. It only quantitatively evaluates the corrosion resistance by measuring the changes in conventional parameters such as weight, size, and mechanical properties before and after the material is immersed. It is difficult to deeply reveal the microscopic changes and mechanisms in the corrosion process. Traditional electrochemical tests can obtain important parameters such as the corrosion rate, electrochemical impedance, and anodic polarization curve of the material, which is of great significance for analyzing the corrosion mechanism of the material. However, relying solely on electrochemical testing, it is impossible to directly observe the corrosion morphology changes of the material, and there is a lack of intuitive understanding of the formation process and microstructural changes of corrosion products. This leads to an incomplete understanding of the corrosion process and makes it difficult to fully evaluate the actual corrosion performance of the material in the marine environment. Summary of the invention

[0006] The purpose of the present invention is to provide a method for testing the corrosion performance of SiC fiber reinforced titanium-based composite materials in a marine environment to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for testing the corrosion performance of SiC fiber reinforced titanium-based composite materials in a marine environment comprises the following steps:

[0009] S1. Preparation of SiC fiber reinforced titanium matrix composite material samples:

[0010] SiC fiber reinforced titanium matrix composite material was selected and cut into rectangular specimens with dimensions of 10 mm × 10 mm × 5 mm;

[0011] S2. Immersion experiment:

[0012] The samples were immersed in different marine environments to evaluate the corrosion performance of SiC fiber reinforced titanium matrix composites in different marine environments.

[0013] S3. Electrochemical test:

[0014] The electrochemical test method was used to test the SiC fiber reinforced titanium matrix composite material samples to obtain the electrochemical performance parameters;

[0015] S4. Microstructure analysis:

[0016] Microscopic analysis methods, including but not limited to scanning electron microscopy and transmission electron microscopy, are used to analyze the microstructure of SiC fiber reinforced titanium matrix composites from different angles and study the microscopic mechanism of corrosion in different marine environments.

[0017] Preferably, the different marine environments in S2 include seawater of different concentrations and solutions of different pH values, and the seawater concentration is selected from five different concentrations of seawater reagents, namely, 5%, 10%, 15%, 20% and 25%.

[0018] Preferably, the electrochemical testing method in S3 includes but is not limited to electrochemical impedance spectroscopy and anodic polarization curve method, wherein during the test, the control conditions include but are not limited to the test conditions, the test conditions include but are not limited to potential and current, and the test data is recorded, and the potential range in the test conditions is -0.2V to 1.2V, and the scanning rate is 0.5mV / s.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts a variety of test methods to comprehensively and accurately evaluate the corrosion performance of SiC fiber reinforced titanium-based composite materials in different marine environments. Through immersion experiments and electrochemical tests, parameters such as the corrosion rate, electrochemical impedance, and anodic polarization curve of SiC fiber reinforced titanium-based composite materials can be obtained, providing more scientific data support for related research. At the same time, by adopting different microscopic analysis methods, the corrosion mechanism under different marine environments can be further studied, providing more reliable data support for the application of SiC fiber reinforced titanium-based composite materials in the field of marine engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a diagram showing the distribution of the SiC reinforcement phase in the Ti alloy in Example 1 of the present invention;

[0022] Figure 2 This is an EDS surface scan of the SiC reinforcement region and the Ti alloy region in Example 1 of the present invention;

[0023] Figure 3 These are EIS-Bode graphs of the SiC-Ti alloy in Example 1 of the present invention after different corrosion cycles in a pure water corrosion environment (a) and a 3.5 wt. % NaCl corrosion environment (b). DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] Material characterization: SiC reinforced Ti55531 (hereinafter referred to as SiC-Ti alloy) was selected as the test material, and the surface microstructure and structure of the material were characterized using an optical microscope (OM).

[0027] Scanning electron microscopy (SEM) equipped with energy dispersive spectrometer (EDS) was used to characterize the cross-sectional structure and composition distribution of SiC-Ti alloy, and to clarify the position and distribution of SiC reinforcement phase in titanium alloy.

[0028] Corrosive environment simulation:

[0029] The wet-dry alternating test (CCT) was used to simulate the service corrosion environment. 2 The sample was wetted with 3.5wt.% NaCl solution to form a liquid film about 400μm thick, and placed in an environment of 25℃ and 80%RH for 12h. The liquid film on the sample surface was completely evaporated in the air to complete a CCT cycle. Then 40μL·cm 2 Ultrapure water dissolves the surface NaCl particles to re-wet them, and then puts them in the same temperature and humidity environment. Parallel CCT tests are performed with ultrapure water at the same time. Samples are taken out at 15CCT and 60CCT for subsequent corrosion resistance characterization.

[0030] Sample processing and testing

[0031] After taking out the SiC-Ti alloy from the CCT experiment, the NaCl particles on the alloy surface were cleaned by ultrasonic cleaning.

[0032] Electrochemical methods (electrochemical impedance spectroscopy and polarization curve measurements) were used to characterize the corrosion resistance of the oxide film on the surface of titanium alloy, and the test adopted a three-electrode system.

[0033] Figure 1 These are the optical microscopy characterization results of the SiC-Ti alloy cross section.

[0034] It can be seen that the SiC reinforcement phase is uniformly distributed inside the Ti alloy. It can also be observed that since the SiC reinforcement phase is encapsulated into the Ti alloy through a compaction process, there are obvious micropores or cracks at the interfaces between different SiC reinforcement phases.

[0035] EDS scan was performed on the interface between SiC reinforcement area and Ti alloy area. Figure 2 As shown in the figure, it can be seen that the SiC reinforcement phase contains W, and there is a significant difference in the composition between the internal SiC reinforcement area and the external Ti alloy area. This is mainly manifested in that the SiC reinforcement phase area contains a more obvious Cr element, and the external Ti alloy area contains a more obvious V element.

[0036] Figure 3 The EIS-Bode diagrams of SiC-Ti alloys obtained at different CCT cycles, where the corrosive medium used in the experimental conditions corresponding to (a) is pure water, and the corrosive medium used in the experimental conditions corresponding to (b) is 3.5wt.% NaCl. It can be seen that when the SiC-Ti alloy is corroded under pure water, the oxide film on the surface of the SiC-Ti alloy becomes denser and more corrosion-resistant; when the SiC-Ti alloy is corroded under the NaCl liquid film for 15CCT, the oxide film on the surface of the SiC-Ti alloy grows, which helps to improve the corrosion resistance. However, with the increase of CCT cycles, after 60CCT corrosion cycles, the oxide film on the surface of the SiC-Ti alloy begins to fail.

[0037] It is worth noting that although the corrosion resistance of SiC-Ti alloy is reduced when corroded at 60CCT under 3.5wt.% NaCl, its corrosion resistance is still higher than that of the substrate, which is related to the growth of oxide film on its surface.

[0038] Implementation 2:

[0039] SiC reinforced Ti55531 (SiC-Ti alloy) was selected as the test material. It was cut into rectangular specimens using high-precision cutting equipment, and the size was strictly controlled to 10mm×10mm×5mm, ensuring that the dimensional accuracy of each specimen was within ±0.1mm to ensure the consistency and accuracy of the experiment. After the cutting was completed, the surface of the specimen was polished with sandpaper, and 200#, 400#, 600#, 800# and 1000# sandpaper were selected in turn. The polishing direction of each sandpaper was consistent, and the polishing time was not less than 2 minutes, so that the surface of the specimen was flat and smooth, without obvious scratches and defects, to avoid the influence of surface roughness differences on the experimental results.

[0040] Corrosion environment simulation

[0041] The dry-wet alternating test (CCT) is used to simulate the service corrosion environment:

[0042] Configure 40μL·cm 23.5wt.% NaCl solution, use a micropipette to accurately measure the solution and evenly wet the sample, ensuring that a liquid film with a thickness of about 400μm (measured by optical interferometry, the error is controlled within ±20μm) is formed on the sample surface. The sample is quickly transferred to an environmental test chamber with a temperature precisely controlled at 25°C (accuracy of ±0.5°C) and a relative humidity stable at 80% (accuracy of ±2%), and allowed to stand for 12h. During this period, humidity sensors and temperature recorders are used to continuously monitor environmental parameters to ensure stable environmental conditions. After the liquid film on the sample surface evaporates completely and naturally in the air, it is marked as a CCT cycle completed.

[0043] Then, a micropipette was used to drop 40 μL cm onto the sample surface. 2 Ultrapure water was used to fully dissolve the NaCl particles precipitated on the surface and the sample was re-wetted. The sample was placed in the same temperature and humidity environment test chamber again and the above process was repeated for subsequent cycles. At the same time, a parallel CCT test using ultrapure water as a "corrosion solution" was carried out according to the same steps. At 15CCT and 60CCT, the sample was carefully removed using tweezers to avoid additional damage to the sample, and the subsequent corrosion resistance characterization was immediately carried out.

[0044] Material characterization

[0045] Use optical microscopy (OM) to characterize the surface microstructure and structure of materials:

[0046] The polished sample was properly polished by chemical mechanical polishing, and the polishing liquid was alumina suspension. The polishing time was 10-15 minutes, and the rotation speed was controlled at 100-150rpm, so that the sample surface reached mirror finish. Then the sample was placed under an optical microscope for observation, and the magnification was gradually increased from 100× to 1000×, and the distribution of SiC reinforcement phase inside the Ti alloy was recorded in detail. The observation results showed that the SiC reinforcement phase was evenly distributed inside the Ti alloy, and obvious micropores or cracks were clearly visible at the interface between different SiC reinforcement phases. The average width of the micropores or cracks was measured using image analysis software, which was about 2-5μm.

[0047] The cross-sectional structure and composition distribution of SiC-Ti alloy were characterized by scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS):

[0048] The samples were inlaid, ground and polished to prepare high-quality cross-sectional samples. Epoxy resin was used as the inlay material, the inlay pressure was 50-80MPa, and the curing time was 24-48 hours. The grinding process used 200#, 400#, 600#, 800# and 1000# sandpapers in turn, and the grinding time of each sandpaper was 5-10 minutes. Finally, 0.5μm diamond polishing paste was used for polishing, and the polishing time was 15-20 minutes. The prepared cross-sectional samples were placed under a scanning electron microscope and observed under an accelerating voltage of 15-20kV, and an energy spectrometer was used to perform EDS scanning on the interface between the SiC reinforcement area and the Ti alloy area. The results show that the SiC reinforcement phase contains W components, and there are obvious differences in the composition of the internal SiC reinforcement area and the external Ti alloy area. Quantitative analysis by energy spectrum analysis software shows that the Cr element content in the SiC reinforcement phase area is about 5%-8%, while the V element content in the external Ti alloy area is about 3%-6%.

[0049] Sample processing and testing

[0050] After taking out the SiC-Ti alloy from the CCT experiment, put the sample into an ultrasonic cleaning machine filled with an appropriate amount of anhydrous ethanol, set the ultrasonic frequency to 40kHz, the power to 100-150W, and the cleaning time to 10-15 minutes to ensure that the NaCl particles on the surface of the alloy are cleaned. After cleaning, use a hair dryer with cold air to dry the sample to avoid residual moisture on the surface of the sample from interfering with subsequent tests.

[0051] Electrochemical methods (electrochemical impedance spectroscopy and polarization curve measurement) are used to characterize the corrosion resistance of the oxide film on the surface of titanium alloy. The test adopts a three-electrode system:

[0052] The working electrode is the treated SiC-Ti alloy sample, which is connected and sealed with a copper wire to ensure good contact between the wire and the sample and no electrolyte leakage. The auxiliary electrode is a platinum sheet electrode with an area of ​​1-2 cm 2 , soak in nitric acid for 10-15 minutes before use, then rinse with deionized water to remove surface impurities and oxides. The reference electrode is a saturated calomel electrode (SCE), connected to the electrolytic cell through a salt bridge, the salt bridge is filled with saturated KCl solution, and the tip of the salt bridge is about 2-3 cm away from the surface of the working electrode to reduce the influence of the liquid junction potential on the test results.

[0053] Electrochemical impedance spectroscopy measurements:

[0054] The electrolyte is 3.5wt.% NaCl solution with a volume of 100-150mL, placed in the electrolytic cell, and the three-electrode system is installed on the electrolytic cell to ensure that the electrode is immersed in the solution to a moderate depth and fixed. Use an electrochemical workstation and start measuring after stabilizing at open circuit potential for 30-60 minutes. The frequency range is set to 10-2 -10 5 Hz, and the AC excitation signal amplitude is 10mV. During the measurement process, the impedance data is monitored and recorded in real time, and the measurement time at each frequency point is not less than 3 seconds to ensure the accuracy of the data. The EIS-Bode diagram is drawn based on the measured impedance data to analyze the impedance change law of the oxide film layer on the surface of the SiC-Ti alloy under different CCT cycles.

[0055] Polarization curve measurement:

[0056] The above three-electrode system and electrolyte were also used. The potential scan range was set to -0.2V~1.2V and the scan rate was 0.5mV / s on the electrochemical workstation. Before scanning, the system was stabilized at the open circuit potential for 10-15 minutes. During the scan, the current-potential curve data was recorded, and the data acquisition frequency was 1-2Hz. By analyzing the polarization curve, the corrosion potential, corrosion current density and other parameters were obtained to further evaluate the corrosion rate and corrosion resistance changes of SiC-Ti alloy under different CCT cycles.

[0057] Embodiment three:

[0058] A method for testing the corrosion performance of SiC fiber reinforced titanium matrix composites in marine environment:

[0059] Sample preparation: SiC fiber reinforced titanium-based composite materials were selected and processed into rectangular samples with a length of 10 mm, a width of 10 mm, and a height of 5 mm using high-precision cutting equipment. The flatness of the cutting surface was controlled within ±0.02 mm. After cutting, the sample surface was polished in turn with 200#, 400#, 600#, 800#, and 1000# sandpapers. The polishing time for each sandpaper was 3 minutes, and the polishing direction was consistent, so that the sample surface was smooth without obvious scratches and processing marks.

[0060] Immersion experiment: Seawater simulation liquid: Accurately weigh 25g NaCl and dissolve it in 500mL deionized water to prepare a 5% concentration of seawater simulation liquid. Use an electronic balance with an accuracy of 0.01g to weigh the mass of NaCl and stir it thoroughly to make it completely dissolved.

[0061] Solutions with different pH values: Use 1 mol / L HCl and 1 mol / L NaOH solutions to adjust the pH value of deionized water. Prepare 500 mL of solutions with pH values ​​of 4, 7, and 10, respectively. Use a pH meter with an accuracy of 0.01 to measure and calibrate the pH value of the solution.

[0062] Immersion operation: Place the prepared samples in the above solutions respectively, with 5 samples placed in each solution, ensuring that the samples are completely immersed and do not touch each other. Immerse in a constant temperature environment box at 25°C for 30 days. During the immersion process, observe the solution color, transparency changes and sample surface conditions every 3 days, and record whether there is corrosion product generation or shedding.

[0063] Post-immersion treatment and analysis: After immersion, take out the sample, rinse it with deionized water for 3 times, and then use filter paper to absorb the surface moisture. Use an electronic balance with an accuracy of 0.0001g to weigh the mass of the sample after immersion, and calculate the mass loss rate. The formula is: [(mass before immersion - mass after immersion) / mass before immersion] × 100%. Use a caliper with an accuracy of 0.01mm to measure the dimensional change of the sample, calculate the volume change rate, and evaluate the corrosion degree of the material.

[0064] Electrochemical test: Electrode preparation, working electrode: The immersed sample was used as the working electrode and encapsulated with epoxy resin, leaving 0.5 cm 2 Before packaging, the sample surface was lightly polished with 400# sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes (ultrasonic frequency 40kHz) to remove the surface oxide layer and impurities. Auxiliary electrode: The area is 3cm 2 The platinum electrode was soaked in aqua regia for 5 minutes before use, and then rinsed with deionized water. Reference electrode: Saturated calomel electrode (SCE) was selected and connected to the electrolytic cell through a Luggin capillary, with the tip of the capillary 1 mm away from the surface of the working electrode.

[0065] Electrochemical impedance spectroscopy (EIS) test: Electrolyte: Use the above-configured 5% seawater simulation solution and a solution with a pH value of 7 as the electrolyte, and pour them into 100 mL electrolytic cells respectively.

[0066] Test process: Install the three-electrode system on the electrolytic cell and set the parameters on the electrochemical workstation. Start the measurement after stabilizing at the open circuit potential for 30 minutes. The frequency range is 10 -2 -10 5 Hz, the amplitude of the AC excitation signal was 5 mV, the measurement time at each frequency point was 3 seconds, the impedance data was recorded and the EIS-Bode diagram and Nyquist diagram were drawn, and the charge transfer resistance (Rct) and double layer capacitance (Cdl) were obtained by equivalent circuit fitting analysis.

[0067] Anodic polarization curve test: Using the above three-electrode system and electrolyte, the potential scanning range was set to -0.5V to 1.5V (relative to the open circuit potential) on the electrochemical workstation, and the scanning rate was 0.1mV / s. Before scanning, the electrode was stabilized at the open circuit potential for 20 minutes. During the scanning process, the current-potential curve data was recorded, and the corrosion potential (Ecorr), corrosion current density (Icorr) and other parameters were calculated by the Tafel extrapolation method.

[0068] Microstructure analysis: Scanning electron microscope (SEM) analysis

[0069] Representative samples were selected from the samples after immersion test and electrochemical test, cleaned with anhydrous ethanol and dried. The samples were fixed on the scanning electron microscope sample stage and gold-sprayed with a thickness of about 8 nm. The microscopic morphology of the surface and cross section of the samples was observed using a scanning electron microscope at different magnifications such as 500×, 1000×, and 5000× to analyze the morphology, distribution, and microstructural changes of the corrosion products, with a focus on the interface bonding between SiC fiber and titanium matrix.

[0070] Transmission electron microscopy (TEM) analysis: For some key samples, the focused ion beam (FIB) technology was used to prepare the transmission electron microscopy samples, and the sample thickness was controlled at about 80nm. The prepared TEM samples were placed in the transmission electron microscope, and the microscopic lattice structure, dislocation distribution, and atomic diffusion between SiC fibers and titanium matrix of the material were observed under the condition of an acceleration voltage of 200kV, so as to deeply explore the microscopic mechanism of the corrosion process.

[0071] In summary, the present invention adopts a variety of test methods to comprehensively and accurately evaluate the corrosion performance of SiC fiber reinforced titanium-based composite materials in different marine environments. Through immersion experiments and electrochemical tests, parameters such as the corrosion rate, electrochemical impedance, and anodic polarization curve of SiC fiber reinforced titanium-based composite materials can be obtained, providing more scientific data support for related research. At the same time, by adopting different microscopic analysis methods, the corrosion mechanism under different marine environments can be further studied, providing more reliable data support for the application of SiC fiber reinforced titanium-based composite materials in the field of marine engineering.

[0072] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.

[0073] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for testing the corrosion performance of SiC fiber reinforced titanium-based composite materials in a marine environment, characterized in that: The following steps are involved: S1. Preparation of SiC fiber reinforced titanium matrix composite material samples: SiC fiber reinforced titanium matrix composite material was selected and cut into rectangular specimens with dimensions of 10 mm × 10 mm × 5 mm; S2. Immersion experiment: The samples were immersed in different marine environments to evaluate the corrosion performance of SiC fiber reinforced titanium matrix composites in different marine environments. S3. Electrochemical test: The electrochemical test method was used to test the SiC fiber reinforced titanium matrix composite material samples to obtain the electrochemical performance parameters; S4. Microstructure analysis: Microscopic analysis methods, including but not limited to scanning electron microscopy and transmission electron microscopy, are used to analyze the microstructure of SiC fiber reinforced titanium matrix composites from different angles and study the microscopic mechanism of corrosion in different marine environments.

2. The method for testing the corrosion performance of SiC fiber reinforced titanium-based composite materials in a marine environment according to claim 1, characterized in that: The different marine environments in S2 include seawater of different concentrations and solutions of different pH values, and the seawater concentrations are selected from five different concentrations of seawater reagents, namely, 5%, 10%, 15%, 20% and 25%.

3. The method for testing the corrosion performance of SiC fiber reinforced titanium-based composite materials in a marine environment according to claim 1, characterized in that: The electrochemical testing method in S3 includes but is not limited to electrochemical impedance spectroscopy and anodic polarization curve method, wherein during the test, the control conditions include but are not limited to the test conditions, the test conditions include but are not limited to potential and current, and the test data is recorded, and the potential range in the test conditions is -0.2V to 1.2V, and the scanning rate is 0.5mV / s.